Allelopathic and Biochemical Characteristics of the Root Environment of Asimina triloba (L.) Dunal - Pavliuchenko, Nataliia Anatoliyivna; Klymenko, Svitlana; Dobroskok, Vitaliy; Krupa, Sergiy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The paper is devoted to the study of the allelopathic and biochemical characteristics of the root environment of Asimina triloba (L.) Dunal (pawpaw) introduced from North America to M.M. Gryshko National Botanical Garden of NAS of Ukraine. The plants were divided into the following age groups: a) young plants (2–4 years old), b) plants of the middle age (5–7 years old), c) the old plants (14–16 years old) and d) the oldest plants (over 22 years old). Allelopathic and biochemical analyses were conducted in dynamics on phases of plant development during flowering, fruitage and the end of the growing season. Rhizosphere soil samples were collected at 0–20 cm layer. The fallow soil was used as a control. The presence of allelochemicals in root environment of A. triloba by modified Neubauer and Schneider method was established. As a result, the inhibition of the growth processes and accumulation of dry matter in the roots and shoots of acceptor plants with an increase in the age of pawpaw was observed. Biochemical state of the root environment was assessed by redox potential (Eh) values. The redox status varied from weakly to highly reducing soil conditions during the growing season. The lowest soil Eh level for the oldest plants was determined. The predominance of reduction processes in the rhizosphere soil of A. triloba indicates the accumulation of mobile organic compounds, which can function as allelochemicals. The content of phenolic compounds in the rhizosphere soil of A. triloba was 1.3–3.0 times higher than control. The concentration of phenolic allelochemicals increased with the age of plants, and also at the end of the growing season. Thus, A. triloba forms a powerful allelopathic regime of the root environment, which is due to the accumulation of free organic compounds, mainly phenolic nature.